CORAL: Similar Outcomes with Intervention, Medical Therapy in Renal Stenosis - Mosley, Mary (MD Conference Express, 2015)
Revascularization with stenting added to optimal medical therapy did not prevent clinical events in patients with atherosclerotic renal artery stenosis in the prospective, randomized, open-label, international, multicenter Cardiovascular Outcomes in Renal Atherosclerotic Lesions (CORAL) study. This article details the results.